2012
DOI: 10.1097/cmr.0b013e328357076c
|View full text |Cite
|
Sign up to set email alerts
|

Temporally designed treatment of melanoma cells by ATRA and polyI

Abstract: In the last three decades, the incidence of melanoma has increased worldwide and no effective treatment modalities have been developed yet. All-trans retinoic acid (ATRA) and polyinosinic:polycytidylic acid (polyI:C) are strong inducers of toll-like receptor 3 (TLR3) and MDA5 expression, and polyI:C-induced TLR3 and MDA5 signaling specifically causes cell death in melanoma cells in vitro. We addressed the question of whether ATRA pretreatment could enhance the efficacy of polyI:C and, if so, would ATRA have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…Importantly, in consistence with the in vitro studies, MDA5 and TLR3 expression in tumor tissues also showed a synergistic effect on NB patient survival. The complementary roles of TLR3 and MDA5 have also been demonstrated in other studies with melanoma and NK cells [ 16 , 17 ]. These lines of evidence strongly support the potential role of targeting innate immune system in the treatment of NB.…”
Section: Discussionsupporting
confidence: 58%
“…Importantly, in consistence with the in vitro studies, MDA5 and TLR3 expression in tumor tissues also showed a synergistic effect on NB patient survival. The complementary roles of TLR3 and MDA5 have also been demonstrated in other studies with melanoma and NK cells [ 16 , 17 ]. These lines of evidence strongly support the potential role of targeting innate immune system in the treatment of NB.…”
Section: Discussionsupporting
confidence: 58%
“…Other existing treatments, such as lapatinib with doxorubicin,[88] all-trans retinoic acid (ATRA), [89] and existing chemotherapies[90, 91] have been reported to exert therapeutic effects through the CXCL9, -10, -11/CXCR3 axis, suggesting that activation of CXCL9, -10, -11/CXCR3 axis may increase efficacies of cytotoxic and targeted therapies. (Table 2)…”
Section: Cxcl9 Cxcl10 Cxcl11/cxcr3 Axis An Enhancer For Other Immumentioning
confidence: 99%
“…In vitro DMT administration has shown an increase of secreted interferons (beta and gamma) in vitro in NK cell and dendritic cell cultures. Interferons are potent anticancer factors (Caraglia et al, 2009; Gonzalez-Navajas et al, 2012; Szabo et al, 2012; Windbichler et al, 2000). If DMT does increase interferon secretion, it may be beneficial in contributing to or aid in better elimination of malignant and/or infected cells.…”
Section: Effects On Other Organ Systemsmentioning
confidence: 99%